Production of Nanocellulose Filter Paper For Water Purification From Malaysian Sustainable Forest Resources (Shorea Roxburghii) Through High-Performance Filtration in Industrial Wastewater Treatment - Abdul Hamid, Nor Hazren; Zulkifli, Nooranisa; Harun, Hasnida; Mohamed Sunar, Norshuhaila; Ali, Roslinda; Hamidon, Nuramidah; Ahmad, Faridahanim (Progress in Engineering Application and Technology, 2020)
Nanostructured cellulose has received enormous attention due to its unique properties. Being the most abundant organic polymer on earth, cellulose is the most suitable candidate for alternative replacement of petroleum-based products. Therefore, this study aims to identify the effectiveness of filter paper using renewable forest resources and the advances made in nanotechnology, especially cellulosic nanomaterials, to develop novel or superior products with enhanced performance attributes. Shorea roxburghii was used as a raw material for the production of nanocellulose filter paper intended use in water purification for the dye removal in textile wastewater. Reactive dyes were considered to be the most problematic compound in textile wastewater due to their high water solubility, high stability and persistence in nature. This study was carried out for the utilization of nanofibrillated cellulose (NFC) filter paper as adsorbent for the removal of dyes from wastewater and to establish it as a standard wastewater treatment process for composite textile industry. Based on the researcher’s study on nanocellulose filter paper, this absorbent was capable of being used as a dye removal.